Prominent Numbers and Ratios in Exchange Rate Determination: Field and Laboratory Evidence - Jürgen von Hagen; Sebastian Kube; Johannes Kaiser; Reinhard Selten; Robin Pope (University of Bonn, Bonn Graduate School of Economics (BGSE), 2006)
In the decision-making process, there is a stage when choosers evaluate alternatives. Evaluation is complex especially when it involves the future exchange rate. In the complexity of predicting the future exchange rate, choosers may use prominent numbers and ratios. We furnish field and experimental evidence of major effects on exchange rate determination from prominent numbers and ratios that constitute nominal equalities and historical benchmarks. Theorizing and estimation of exchange rates can be enhanced via SKAT, the Stages of Knowledge Ahead Theory that allows prominent numbers and prominent ratios to be taken into account consistently in constructing decision models.
Keywords: D80; D81; F31; F33; 330; nominalism; money illusion; unpredictability; experiment; SKAT the Stages of Knowledge Ahead Theory; prominent numbers; prominent ratios